DARE Newsletter, Vol. 13, No. 4, Fall 2010 - Hall, Joan Houston; Buss, Dale; DARE; Sorenson, Jon E. (Dictionary of American Regional English, 2010)
Contents: "DARE in the News" by Joan Houston Hall; "DARE to Be Finished--Maybe Next Year" by Dale Buss; "Funding Update" by Jon E. Sorenson; "Coming in Volume V"; "How to Speak American" by Joan Houston Hall; "DARE Board at the Department of the Interior"; "Where Are They Now?--Scot LaFaive"; "In Memoriam: James J. Kilpatrick"; "Snapshots and Schnibbles"; "DARE on Twitter"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Lexicography; Regional English; English Language--Dialects--United States